Mitochondrial Dysfunction in Metabolic Disease - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Mitochondrial function and behavior are central to the physiology of humans and, consequently, "mitochondrial dysfunction" has been implicated in a wide range of disease.CONTENT: Mitochondrial ROS might attack various mitochondrial constituents, causing mitochondrial DNA mutations and oxidative damage to respiratory enzymes. A defect in mitochondrial respiratory enzymes would increase mitochondrial production of ROS, causing further mitochondrial damage and dysfunction. Mitochondrial dysfunction is associated with diseases, such as neurodegenerative disorders, cardiomyopathies, metabolic syndrome, obesity, and cancer. Pathways that improve mitochondrial function, attenuate mitochondrial oxidative stress, and regulate mitochondrial biogenesis have recently emerged as potential therapeutic targets.SUMMARY: Mitochondria perform diverse yet interconnected functions, produce ATP and many biosynthetic intermediates while also contribute to cellular stress responses such as autophagy and apoptosis. Mitochondria form a dynamic, interconnected network that is intimately integrated with other cellular compartments. It is therefore not suprising that mitochondrial dysfunction has emerged as a key factor in a myriad of diseases, including neurodegenerative, cancer, and metabolic disorders. Interventions that modulate processes involved in regulation of mitochondrial turnover, with calorie restriction and induction of mitochondrial biogenesis, are of particular interest.KEYWORDS: mitochondrial biogenesis, mitochondrial dysfunction, reactive oxygen species (ROS), metabolic diseases